Analisis Pengaruh SIM, SOP dan Jaringan Distribusi Terhadap Supply Chain Manajemen (Studi Kasus Pada PT. Lion Mentari Airlines) - Aliffah Kusumaningrum (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
To improve realibility and air worThere are several factors that could lead supply chain effectively, like information systems, implementation standard operating procedures and distribution network. Maintenance of air plane can be go efferective and efficient to support supply chain such as system Information,standard operating procedure,supply chain. The factor of regulation in an airlines not only involved by employees in their work environment but also support by the tight of regulation itself. The objective of this paper is to finding out whether three of factor above have impacting supply chain effectively (as partial and collective) and also define what factor that strongest affecting supply chain effectively. This study is a survey to test the hypothesis of the influence between Management Information Systems, standard operating procedures and distribution networks on the effectiveness of supply chain in the airlines PT. Lion Mentari Airlines, and the results of the survey through the questionnaire were analyzed through hypothesis testing carried out by the method of correlation and regression. the results of the analysis and testing in the study of the factors that influence the supply chain effectiveness in PT Lion Mentari Airlines, the following conclusions are obtained, the analysis shows a significant influence between management information systems on supply chain effectiveness, which means that the higher the effectiveness of information systems Management, the higher the supply chain operational effectiveness. This shows that information systems can help activities and improve the achievement of operational objectives for the company.